Assessment of textbook oncologic outcomes following pancreaticoduodenectomy for pancreatic adenocarcinoma. Issue 6 (2nd March 2020) - Sweigert, Patrick J.; Eguia, Emanuel; Baker, Marshall S.; Paredes, Anghela Z.; Tsilimigras, Diamantis I.; Dillhoff, Mary; Ejaz, Aslam; Cloyd, Jordan; Tsung, Allan; Pawlik, Timothy M.
Abstract: Background: Composite outcomes may more accurately reflect patient and provider expectations around optimal care. We sought to determine the impact of achieving a so‐called "textbook oncologic outcome" (TOO) among patients undergoing resection of pancreatic adenocarcinoma (PDAC). Methods: Patients undergoing pancreaticoduodenectomy (PD) for PDAC between 2006 and 2016 were identified in the National Cancer Database (NCDB). TOO was defined by: margin negative resection, compliant lymph node evaluation, no prolonged length‐of‐stay, no 30‐day readmission/mortality, and receipt of adjuvant chemotherapy. Factors associated with TOO and overall survival (OS) were evaluated using multivariable logistic and Cox regression models, respectively. Results: Among 18 608 patients who underwent PD at 782 hospitals, many patients successfully achieved certain TOO factors such as R0 margin (77.9%) and no 30‐day mortality (96.9%), while other TOO criteria such as receipt of adjuvant therapy (48.2%) were achieved less frequently. Overall, only 3124 (16.8%) patients achieved a TOO. Factors associated with lower odds of TOO included: older age, Black race, Medicaid insurance, Community facility, and low PD facility (<20 PD/y) (all P < .05). Achievement of a TOO was associated with lower risk of mortality (HR 0.74; 95% CI, 0.70‐0.77). Conclusions: While TOO was associated with improved long‐term survival, TOO was only achieved in 16.8% of patients undergoing PD.